MERCOSUR and Chile : the FTAA's other pole? - Quijano, José Manuel (2001)
Focuses on the current relations between the two largest trade blocs in the Western Hemisphere, namely MERCOSUR+Chile and the NAFTA. Examines the benefits and drawbacks that could arise from the integration of these two groups of countries into a common free trade area.